Instrumental intelligent platforms for criminal analysis - V. M. Strukov; Y. V. Gnusov; Y. V. Gnusov (Law and Safety)
The aim of the work is a comparative analysis of the most well-known foreign and domestic intelligent data mining platforms for criminal analysis. The relevance of this work is due to the peculiarities of the Fourth Industrial Revolution, the processes of which are rapidly unfolding at the present stage and have a critical impact on all areas, including law enforcement. Such features include: 1) "information explosion", which is intensifying, 2) accelerating the pace of development of modern technologies; 3) the cost of high-tech tools, which is rapidly declining, and such tools become available to ordinary citizens (including criminals). The consequences of illegal actions of perpetrators with the use of modern high-tech tools are analyzed. It is determined that the consequences of such actions can be large-scale, forcing law enforcement agencies around the world to move from a reactive to a predicative model of activity. A fundamentally important condition for the implementation of the predicative model is the use of highly intelligent tools to prevent crime. An analytical review of the most modern intellectual platforms used for the needs of criminal analysis and meeting modern requirements for such systems is given. Based on the review of existing platforms of criminal analysis and practical experience, a list of functional components of analytical tools of criminal analyst, which are currently used in various intellectual platforms of criminal analysis and in the practice of law enforcement was formulated. Typical features of intelligent software of law enforcement agencies in general and criminal analysis in particular are highlighted. A comparative overview of the functionality of analytical tools of intelligent software of law enforcement agencies of foreign countries and domestic developments is given. Features of functional components of intellectual systems of criminal analytics are named. Based on the study, the requirements for the functional characteristics of intelligent systems of automated analysis for the needs of criminal analysis are formulated. Using the results of this study will provide an opportunity at the stage of choosing the necessary platform to formulate requirements for its functional content.